(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In winter 2022–2023, a study titled "Studies on N.P.K and organic manure on plant growth and establishment of dragon fruit (Hylocereus polyrhizus) under Kanpur agro climatic condition" cv. Red Flesh was carried out at the research farm of the Department of Horticulture, Rama University, Kanpur